Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species - Cao, Yanghui; Yang, Meixia; Zhang, Yalin (Zootaxa, 2016)
Generic characteristics of genus Alnetoidia Dlabola are revised based on study of nine species from China, including two new species: A. (Alnetoidia) gracilis, A. (Alnella) dentata spp. nov., and four new records to China. A key to species for identification of Chinese adult males is provided.